Dynamic Recrystallization of Wrought–Solidified–Wrought Complex Structure in Ni‐Based Superalloys1. Issue 5 (29th August 2014) - Ning, Yongquan; Xie, Bingchao; Li, Hui; Fu, Ming Wang
<x xml:space="preserve">Abstract</x> Electron beam welding is conducted on the as‐polished Ni‐base superalloys. The wrought–solidified–wrought (W–S–W) complex structure was machined from the central part of the weldments, and the hot compression test of W–S–W was then conducted. The DRX activation energy was calculated, and a constitutive equation which describes the DRX occurrence in hot working process was established. The deformed substructures such as dense dislocation networks were observed in the deformed dendrites in the welding seam of W–S–W. When the solidified dendrite in the welding seam is entirely covered with the recrystallized grains, the first necklace microstructure is formed. The dislocations drive the occurrence of DRX again in the first necklace microstructure. When several necklaces were formed, the solidified dendrite in the welding seam disappeared. The area fraction of DRX increases with increasing height reduction. The solidified dendrite could be greatly eliminated and refined after severe plastic deformation due to the repeating occurrence of DRX.